Temperature-dependent development of Anisopteromalus calandrae (Howard) (Hymenoptera: Pteromalidae) parasitizing Lasioderma serricorne (F.) (Coleoptera: Anobiidae). (January 2022) - Guo, Yafei; Lü, Jianhua; Guo, Jianhua; Xi, Jiaqin; Guo, Chao
Abstract: Inundated release of parasitoids is an environmentally friendly pest insect control method. Deep understanding influence of different temperatures on development of parasitoids is very helpful for improving biological control effectiveness. Thus, the life history parameters of Anisopteromalus calandrae (Howard) (Hymenoptera: Pteromalidae) reared on mature larvae (about 30 days old) of Lasioderma serricorne (F.) (Coleoptera: Anobiidae) were investigated at 15, 20, 25, 30, 35, and 40 °C. Anisopteromalus calandrae completed development with adult emergence at 25, 30, and 35 °C. The developmental rate of A. calandrae increased significantly with increasing temperature, and the favorable temperature for A. calandrae development was 25 °C. The mean generation survival rates were 49.67, 50.33, and 40.00% at 25, 30, and 35 °C, respectively. The developmental threshold temperatures of eggs, larvae, pupae, and preoviposition were 22.55, 18.86, 10.02, and 23.38 °C, respectively, and their effective accumulated temperatures were 5.33, 43.69, 152.48, and 2.90 °C·d, respectively. The present results are in favor of further understanding the biological characteristics of A. calandrae and designing effective biological control protocols. Highlights: Anisopteromalus calandrae could complete the egg-to-adult development at 25, 30, and 35 °C. The rate of A. calandrae development increased significantly with the increasing temperatures. The favorable temperature for A. calandrae development was 25 °C.